Pengenalan Aplikasi Buku Warung Di Era Moderen Bagi Pelaku UMKM Pakaian Di Pasar Beringharjo Dan Condongcatur Di Kota Yogyakarta - Nur Amelia Kasman; Yudas Tadius Andi Candra (Jurnal Kabar Masyarakat, 2023)
The Buku Warung application is an application that can help in recording financial reports efficiently. However, there are still many MSMEs who do not have the knowledge to use this application. The aim of this service is to help MSMEs record their finances online through the Buku Warung application. This application was chosen because recording can be done flexibly and time efficiently without having to record it manually in a book. The method used is a location survey, introduction to the Buku Warung application, training on using the Buku Warung application and final evaluation. The result of this service is that MSMEs are greatly helped in recording financial reports efficiently and flexibly and can be done using a cellphone without having to record manually in a book anymore. The servants hope that this service can continue and that the Buku Warung application can be used well by MSMEs.